Mental Workload Analysis of Employees Using the National Aeronautics and Space Administration Task Load Index (NASA – TLX) Method: (Case Study of CV. XYZ Candi) - Hakim, Luqman; Rizki, Muhammad Maulana; Wulandari, Rina Sri (Journal of Research and Technology, 2025)
CV. XYZ Candi operates in the manufacturing and services sector, particularly the production of industrial machine spare parts. High productivity demands are often directly proportional to increased employee mental workload—problems at CV. XYZ Candi Technical problems, such as frequent chisel breaks, material delays, engineering drawing errors, and material mismatches (materials not centered), also exacerbate the situation. This is further compounded by employee capabilities that are not fully aligned with the task's complexity, as well as a less-integrated workflow system. To analyze this problem comprehensively, the NASA-TLX (Task Load Index) method was chosen as an evaluation tool. NASA-TLX measures mental workload multidimensionally through six indicators: mental demand, physical demand, time requirements, performance, effort level, and frustration level. This method is relevant to apply to a CV. XYZ Candi can identify dominant factors that contribute to workload, such as time pressure, task difficulty, and priority conflicts. Most respondents (57.2%) experienced moderate mental workload, 33.3% high, and 9.5% low mental workload among the 21 employees at CV. XYZ Candi experienced very high mental workloads, with the highest scores influenced by physical demands, time demands, effort levels, and frustration levels.